Enhancing a Client-Centred Practice with the Canadian Occupational Performance Measure. (27th June 2018) - Enemark Larsen, A.; Rasmussen, B.; Christensen, J. R.
Abstract : Background . The active participation of clients is an important aspect of rehabilitation quality as conceptualized in client-centred practice (CCP). A recommended outcome measure for enhancing CCP is the Canadian Occupational Performance Measure (COPM). However, the relationship between COPM use and CCP enhancement has not been documented. Aim . The aim of this study was to examine whether the use of the COPM enhanced CCP. Methods . We performed a scoping review in five steps: (1) identifying a search strategy with inclusion and exclusion criteria; (2) screening relevant databases for published and unpublished studies by using selected keywords and by manually scrutinizing reference lists; (3) agreeing on eligible papers between authors in terms of inclusion and exclusion criteria; (4) charting included data; and (5) analysing data using qualitative content analysis. Results . Twelve studies were included in the review. The results indicated enhanced CCP in two themes when using the COPM. These themes appeared to influence each other; therefore, the first theme, Conditions for enhancing CCP when using the COPM, represented the circumstances needed for the second theme, Enhancing CCP when using the COPM, to be fulfilled. Conclusion. The use of the COPM seems to enhance CCP if certain conditions are present.